School-based mental health promotion: A global policy review - Margaretha, Margaretha; Azzopardi, Peter Sebastian; Fisher, Jane; Sawyer, Susan Margaret (Frontiers in Psychiatry, 2023)
ABSTRACT Objectives. Schools are increasingly recognized as important settings for mental health promotion; however, it is unclear what actions schools should prioritize to promote student mental health and wellbeing. Therefore, we undertook a policy review of global school-based mental health promotion policy documents from United Nations (UN) agencies to understand what frameworks and actions are recommended for schools. Methods. We searched for guidelines and manuals from UN agencies from 2000-2021 using combinations of the following terms: mental health, wellbeing, psychosocial, health, school, manual, framework and guidelines; from the World Health Organization (WHO) library, the National Library of Australia and Google Scholar. Textual data synthesis was undertaken. Results. Fifteen documents met inclusion criteria for review, of which 11 were from WHO and four from other UN agencies. UN policy documents commonly recommend using a comprehensive school health framework that facilitates the integration of actions to prevent, promote and treat mental health problems for the whole school community. These policy documents suggest that the primary role of schools is to build enabling contexts for mental health and wellbeing. Schools should equip themselves with capacities to deliver actions that aim to prevent, promote and treat mental health problems. The conceptualization of comprehensive school health and developing schools as enabling contexts will be discussed further. Implications. As comprehensive health framework around mental health is recommended for all schools, effective implementation of mental health promotion requires actions from governments, school communities (teachers, staff and students), families and communities.